In silico investigation of Cu(In,Ga)Se2-based solar cells - Mirhosseini, Hossein; Raghupathy, Ramya Kormath Madam; Sahoo, Sudhir K.; Wiebeler, Hendrik; Chugh, Manjusha; Kühne, Thomas D. (Physical Chemistry Chemical Physics, 2020)
Photovoltaics is one of the most promising and fastest-growing renewable energy technologies. Although the price-performance ratio of solar cells has improved significantly over recent years, further systematic investigations are needed to achieve higher performance and lower cost for future solar cells. In conjunction with experiments, computer simulations are powerful tools to investigate the thermodynamics and kinetics of solar cells. Over the last few years, we have developed and employed advanced computational techniques to gain a better understanding of solar cells based on copper indium gallium selenide (Cu(In,Ga)Se2). Furthermore, we have utilized state-of-the-art data-driven science and machine learning for the development of photovoltaic materials. In this Perspective, we review our results along with a survey of the field.
CRIS-Team Scopus Importer:2023-03-20